Metode Rancang Optimasi PLTPH Turbin Vortex di Danau Universitas Indonesia Untuk Pemanfaatan Turbin di Pedesaan - Muhammad Raihan Abimanyu; Gun Gun Ramdlan Gunadi; Andi Ulfiana (Jurnal Mekanik Terapan, 2022)
Picco-hydro Power Plant (PLTPH) is a power plant that utilizes water energy to produce small-scale electricity. The power produced starts from tens of watts to 5 Kw. In this study, an economical PLTPH system was designed with the selection of the type of generator according to the mechanical power of the turbine. Turbine mechanical power measured an average of 150-280 Watt with the highest rotation of 135 RPM. Then choose a 300 Watt DC generator with a working ratio of 100-900 RPM. With the selection of cheap after market pulleys and analysis of the size of the transmission ratio, obtained a rotation ratio that can increase the turbine speed up to 810 RPM speed. Then a control panel and simple instruments were made as an electrical stabilizer, protection and measurement of the work of the generating unit. The power generated can turn on 16 DC lamps that have been installed on the lake road, with an optimal power reading of ±31 Watt. If turned on without loading the generator is capable of producing a voltage of up to 44 Volt DC.